Role of electron correlation in the P, T-odd effects of CdH: a relativistic coupled-cluster investigation - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2020)
We investigate the parity (P) and time-reversal (T) symmetry violating effects in the CdH molecule and perform the relativistic coupled-cluster calculation of the molecular parameters-E-eff, W-s, and W-M-related to the electric dipole moment of electron (eEDM) interaction, the scalar-pseudoscalar (S-PS) nucleus-electron neutral current coupling, and the nuclear magnetic quadrupole moment (MQM) interaction with electrons, respectively. We also compute the molecular dipole moment and the magnetic hyperfine structure coupling constant of CdH. The values of E-eff, W-s, and W-M obtained by us in the said molecule are 12.2 GV/cm, 14.0 kHz, and 0.82 x 10(33) Hz/e cm(2), respectively, within an uncertainty of 10%. Furthermore, we study the trend of electron-correlation in the computed properties of CdH and that of the P, T-odd parameters in the group-12 monohydrides (i.e., ZnH, CdH, and HgH).